Reducing Total Power Consumption and Total Area Techniques for Network-on-Chip Through Disable Cores and Routers Based on Clustering Method - Ng Yen Phing; M.N. Mohd Warip; Phaklen Ehkan; S.Y. Teo (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Network-on-Chip (NoC) is a promising solution to overcome the communication problem of System-on-Chip (SoC) architecture. The execution of topology, routing algorithm and switching technique is significant because it powerfully affects the overall performance of NoC. In the Network-on-Chip, the total power consumption increasing due to the large scale of network. In order to solve it, a clustering method and disable cores and routers based on clustering method is apply onto mesh based NoC architecture. In the proposed approach, the optimization of total area and total power consumption are the major concern. Experiment results show that the proposed method outperformas the existing work. The clustering-mesh based method reduced the total area by 22% to 40 % and total power consumption by 22% to 56% compare to mesh topology. In addition, the proposed method by disable cores and routers based on clustering-mesh based method has decrease the total area by 45% to 87% and total power consumption by 33% to 75% compare to mesh topology.